Cannabis Use and the Onset of Cigarette and E-cigarette Use: A Prospective, Longitudinal Study Among Youth in the United States. Issue 3 (24th August 2020) - Weinberger, Andrea H; Zhu, Jiaqi; Lee, Joun; Xu, Shu; Goodwin, Renee D
Abstract: Introduction: Cigarette use is declining among youth in the United States, whereas cannabis use and e-cigarette use are increasing. Cannabis use has been linked with increased uptake and persistence of cigarette smoking among adults. The goal of this study was to examine whether cannabis use is associated with the prevalence and incidence of cigarette, e-cigarette, and dual product use among U.S. youth. Methods: Data included U.S. youth ages 12–17 from two waves of the Population Assessment of Tobacco and Health (PATH) Study (Wave 1 youth, n = 13 651; Wave 1 tobacco-naive youth, n = 10 081). Weighted logistic regression models were used to examine the association between Wave 1 cannabis use and (1) Wave 1 prevalence of cigarette/e-cigarette use among Wave 1 youth and (2) Wave 2 incidence of cigarette/e-cigarette use among Wave 1 tobacco-naive youth. Analyses were run unadjusted and adjusted for demographics and internalizing/externalizing problem symptoms. Results: Wave 1 cigarette and e-cigarette use were significantly more common among youth who used versus did not use cannabis. Among Wave 1 tobacco-naive youth, Wave 1 cannabis use was associated with significantly increased incidence of cigarette and e-cigarette use by Wave 2. Conclusions: Youth who use cannabis are more likely to report cigarette and e-cigarette use, and cannabis use is associated with increased risk of initiation of cigarette and e-cigarette use over 1 year. Continued success in tobacco control—specifically toward reducing smoking among adolescents—may require focusing on cannabis, e-cigarette, and cigarette use in public health education, outreach, and intervention efforts. Implications: These data extend our knowledge of cigarette and e-cigarette use among youth by showing that cannabis use is associated with increased prevalence and incidence of cigarette and e-cigarette use among youth, relative to youth who do not use cannabis. The increasing popularity of cannabis use among youth and diminished perceptions of risk, coupled with the strong link between cannabis use and tobacco use, may have unintended consequences for cigarette control efforts among youth.